Revive Textile and Product Textile Industry Performance Through Improved Implementation of Key Spatial Utilization Program Policies - Ratnasari, Novi Eka; Sumadinata, Widya Setiabudi; Susanti, Elisa (PERSPEKTIF, 2024)
The space utilization program policy, which is realized in preparing indications for the main space utilization program, is the key to achieving spatial planning objectives and a reference in regional development planning. This research aims to examine and analyze how the Bandung Regency Government (Department of Industry and Trade, Regional Planning, Research and Development Agency, Public Works and Spatial Planning Service, and Environmental Service) implements phase 1 space utilization program policies (2017- 2021) based on a combination of rational model and management models dimensions from Khan and Khandaker's policy implementation theory. The method used in this research is descriptive qualitative through interviews with sources using purposive sampling supported by literature from journals, data, and other reports from central and regional governments that are relevant to the research. The results of this research show that the implementation of the space utilization program policy has not been running optimally, so improvements are needed in terms of maintaining consistency between the main space utilization program and regional sectoral programs, through periodic monitoring before the 5-year review, improving the quality of resources in optimizing expenditure budgeting planning capabilities regional areas, building intense communication with SMEs and increasing cooperative connectivity between the TPT industry which functions upstream and downstream in the Bandung Regency area.